2016
DOI: 10.1007/s10995-016-2053-6
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines and Interventions Related to the Postpartum Visit for Low-Risk Postpartum Women in High and Upper Middle Income Countries

Abstract: Objectives A two-part review was undertaken to: (1) summarize current guidelines on the timing and frequency of postpartum follow-up care for generally healthy, non-high risk postpartum women and to delineate the evidence on which these guidelines are based; and, (2) summarize the results of intervention studies focused on increasing utilization of the postpartum visit for generally healthy, non-high risk postpartum women. Methods A review of guidelines from high and upper middle income countries published bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…9,21,22 Continued health care engagement in the postpartum period has the potential to address health concerns among women with OUD, including postpartum depression, breastfeeding support, contraception, and the provision of family planning services. 23 To wit, our study found that Pennsylvania Medicaid expansion in 2015 due to the ACA significantly reduced dis-enrollment following delivery. After Medicaid expansion, 87% of women remained continuously enrolled during the 300 days after delivery, compared with 81% prior to expansion.…”
Section: Discussionmentioning
confidence: 66%
“…9,21,22 Continued health care engagement in the postpartum period has the potential to address health concerns among women with OUD, including postpartum depression, breastfeeding support, contraception, and the provision of family planning services. 23 To wit, our study found that Pennsylvania Medicaid expansion in 2015 due to the ACA significantly reduced dis-enrollment following delivery. After Medicaid expansion, 87% of women remained continuously enrolled during the 300 days after delivery, compared with 81% prior to expansion.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, we tested for multicollinearity to eliminate redundant variables and decided a priori to include ethnicity, age, and parity, which are known predictors of postpartum visit completion, in the logistic regression model. 2,5 We used the REDCap electronic data system for data management 13 and SPSS 24 (IBM, Armonk, NY) for statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the clear expectation of post-birth care planning set-out in policy, there is little evidence of such care plans being utilised in practice. Much of the literature and policy documents quantify women’s experience of postnatal services, that is, describe the number and timing of post-birth visits, rather than discuss the content of visits [41]. Adequate contact from professionals is important in ensuring that women receive appropriate care during the post-birth period [6, 7].…”
Section: Resultsmentioning
confidence: 99%